Benign Bone Tumors about the Hip - Patel, Jay N.; Gianakos, Arianna; Miller, Justin M.; Hoskins, Tyler; Wittig, James C. (The Journal of Hip Surgery, 2019)
Hip pain can often be a challenging patient complaint with a complicated differential diagnosis, in part because there are numerous etiologies of both primary and referred hip pain. It is critical that clinicians be able to properly diagnose and treat these etiologies. Here, the authors present the incidence, characteristics, and treatment of various benign bone tumors around the hip to help clinicians accurately identify these conditions.
Keywords: hip; tumor; orthopaedic oncology; benign